Pengaruh Good University Governance terhadap Mutu Layanan Perpustakaan Perguruan Tinggi di Daerah Istimewa Yogyakarta - Pongmangngatta, Sule Datu; Putriana Kristanti (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the influence of Good University Governance (GUG) on the quality of library services in the Special Region of Yogyakarta. Good University Governance, which encompasses the principles of transparency, accountability, responsibility, independence, and fairness, is believed to contribute to the improvement of service quality, including within university libraries as centers of information and learning. The research object consists of university libraries located in the Special Region of Yogyakarta. Data were collected using a purposive sampling approach, where informants were selected based on specific considerations relevant to the research objectives. The data collection methods included both quantitative and qualitative approaches. The quantitative data were obtained through questionnaires using a Likert scale, while qualitative data were gathered through interviews with several library heads. The findings indicate that transparency, responsibility, and independence have a significant influence on the quality of library services. However, accountability and fairness do not appear to have a significant impact.